The evaluation of ground reaction forces during two different soccer throw-in techniques: A preliminary study - Cerrah, A. O.; Simsek. D.; Ertan, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine the differences in Ground Reaction Forces (GRF) between standing and running soccer throw-in. Six male amateur soccer players participated in the current study. All data are expressed as mean±SD. The longer distance was observed in the running throw-in than the standing throw-in. The standing throw-in showed higher values at Vertical (Fz) GRF during back swing, forward swing and release phases. However, that of the running throw-in during follow through phase was higher than that of the standing throw-in. As a result, the longer throwing distance in the running throw-in can be explained that the players spend shorter time in all phases at running throw-in than they did in the standing throw-in. This might causes efficient energy transfer from proximal to distal segment during the running throw-in.